Solving the puzzle of mercury fate and emissions by coal-fired power plants: The potential of hydrodynamic-atmospheric modelling. (1st November 2021) - Schneider, Larissa; Warren, Maxwell; Lintern, Anna; Winn, Paul; Myllyvirta, Lauri; Beavis, Sara; Gruber, Bernd
Abstract: There is currently a significant gap in knowledge about the emission and deposition of mercury (Hg) from coal-fired power plants in Australia. To fill this gap, we propose a novel method that combines several sources of information (stratigraphic data, hydrodynamic modelling and atmospheric modelling), to identify the sources and fates of Hg emitted from coal-fired power plants. The stratigraphic record from Lake Macquarie (Australia) shows that mercury deposition increased up to 7-times since the 1950s, which is when coal-fired power plants were commissioned in the catchment. The stratigraphy also shows a decrease in Hg deposition with power plant retrofits. Using results from multiple models (statistical modelling, hydrodynamic modelling, particle density modelling and atmospheric emissions modelling), we found that ash dams contribute little Hg to Lake Macquarie. Instead, most of the Hg contamination in the lake is a result of atmospheric emissions from the power plants, and these power plants are also depositing Hg in the urban areas to the west of the lake. Our results demonstrate that the multi-proxy approach demonstrated in the paper can be used to provide clues as to the source of Hg, so that appropriate mitigation strategies and regulatory frameworks can be implemented. Graphical abstract: Image 1 Highlights: Multiple lines of evidence used to identify source and fate of Hg. Hg in aquatic sediments at case study site comes from atmospheric emissions, not ash dams. Hg mitigation strategies at coal-fired power plants should reduce Hg in atmospheric emissions.